PENGARUH KUALITAS AIR TERHADAP PRODUKSI RUMPUT LAUT (Kappaphycus alvarezii) - Andi Ichsan Nur; Husain Syam; Patang Patang (Universitas Negeri Makassar, 2016)
The study aims to determine the effect of water quality on the production of seaweed (Kappaphycus alvarezii). This study was an experimental study using a completely randomized design (CRD). There are three treatments, treatment A (50 m), treatment B (500 m), treatment C (1000 m) and a control consisting of three replications. The research variables were observed include the production and quality of the sea water. The analysis technique used in this research is the analysis of variance were processed using SPSS version 20. The results showed that the location most suitable planting sea grass is at a spacing of 500 meters from the river mouth to the value of the highest average production of 88500g (88,5kg ) while the water quality such as salinity, pH, temperature, turbidity, phosphates and dissolved oxygen, still within acceptable limits for the growth and production of seaweed (Kappaphycus alvarezii)